Socio-economic factors affecting women's entrepreneurial performance in MSEs in Bahir Dar City, Ethiopia - Samuel Godadaw Ayinaddis (Journal of Innovation and Entrepreneurship, 2023)
Women's entrepreneurship is the pillar of economic expansion in many developing countries and is increasingly recognized as an essential driver of economic growth, productivity, innovation, employment, and economic dynamism. This study aimed to investigate the socio-economic factors that affect women's entrepreneurial performance in MSEs in Bahir Dar City, Ethiopia. This study employed explanatory and descriptive survey designs using a quantitative research approach. The data were gathered from a survey of 348 registered women-owned MSEs. Statistical models, including factor analysis, correlation, and regression analysis, were used to look for patterns and relationships between variables apart from other descriptive statistics. Based on the statistical analysis, the variables social, economic, and legal and administrative factors have a positive relationship with women's entrepreneurial performance in MSEs. On the other hand, demographic factors are found to be insignificant variables in predicting women's entrepreneurial performance in MSEs. Therefore, the research recommends improvements in social and economic development to facilitate the successful performance of women entrepreneurs in MSEs in Bahir Dar city, Ethiopia.
Keywords: 650; MSEs; Women entrepreneurs; Performance; Socio-economic factors